Gastric Outlet Obstruction by Trichobezoar, A Case Report - Akhter, SM Quamrul; Reza, Syed Masud; Ahmad, Sami; Lima, Ismat Jahan; Sony, Fayeem Chowdhury; Gupta, Amit Sen; Islam, Md Shafiqul (Journal of Shaheed Suhrawardy Medical College, 2018)
A trichobezoar is a bezoar ( a mass found tapped in the gastrointestinal system) formed from the ingestion of hair. Trichobezoars are often associated with trichotillomania (compulsive hair pulling). Trichobezoars are rare, but can be fatal if undected1,2. Surgical intervention is often required. Gastric outlet obstruction (G.O.O) is one of the presenting complaints of trichobezoars in the stomach. Patients with this condition often have an underlying psychiatric illness & history may not be easily forthcoming. This condition mainly occurs in young female. We are presenting a case of gastric outlet obstruction in a young female of 25 years old. After taking history, clinical examination, necessary investigation it seemed to be a case of trichobezoar. Laparatomy done under general anaesthesia, then opened the stomach and found it was a case of trichobezoar. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 85-87